2006
DOI: 10.4319/lo.2006.51.5.2008
|View full text |Cite
|
Sign up to set email alerts
|

Significance of subcellular metal distribution in prey in influencing the trophic transfer of metals in a marine fish

Abstract: We investigated how the subcellular metal distribution in prey affects metal dietary assimilation in a marine fish, the grunt Terapon jarbua. The assimilation efficiency (AE) of metals (Cd, Se, and Zn) in the grunt varied by prey, which included copepods, barnacles, clams, mussels, and fish viscera. The AEs were 3-9% for Cd, 13-36% for Se, and 2-52% for Zn. The AEs of Se and Zn were significantly correlated with the subcellular Se and Zn distributions in the prey, suggesting that the subcellular forms of Se an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 33 publications
(41 reference statements)
8
80
2
1
Order By: Relevance
“…The ingestion rate (IR, equivalent to FR in the present study) and gut passage time (GPT) are suggested to be the 2 most important factors determining the AEs of metals in many aquatic organisms (e.g. Zhang & Wang 2006a, Croteau et al 2007). In most cases, the AEs of metals increased with prolonged GPT, and AEs were higher at a lower IR and vice versa (Zhang & Wang 2006a, Croteau et al 2007).…”
Section: Feeding Ratio and Frequency Affecting Dietary CD Bioaccumulamentioning
confidence: 99%
See 2 more Smart Citations
“…The ingestion rate (IR, equivalent to FR in the present study) and gut passage time (GPT) are suggested to be the 2 most important factors determining the AEs of metals in many aquatic organisms (e.g. Zhang & Wang 2006a, Croteau et al 2007). In most cases, the AEs of metals increased with prolonged GPT, and AEs were higher at a lower IR and vice versa (Zhang & Wang 2006a, Croteau et al 2007).…”
Section: Feeding Ratio and Frequency Affecting Dietary CD Bioaccumulamentioning
confidence: 99%
“…Although a growing body of study has revealed that changes in food quality have a significant effect on dietary metal assi milation in farmed marine fish (e.g. food type [Wang & Wong 2003, Zhang & Wang 2006a and dietary protein sources [Mai et al 2006), little is known about the influence of food quantity management (e.g. feeding ratio and frequency adjustments) on dietary metal bioaccumulation in farmed fish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in mummichog (Goto and Wallace 2010); brown trout and European eel (Linde et al 1999)), Ni and Tl (e.g. in yellow perch (Campbell et al 2008); fathead minnow (Lapointe and Couture 2009)) and Se (e.g. in grunt (Zhang and Wang 2006)). The benefit of metal and metalloid determination in the soluble tissue fraction over determination of total tissue load lays in the fact that accumulated metals and metalloids, as described for Cd, fractionate into metabolically reactive and detoxified pools.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively the granule fraction may 463 represent selenium associated with incompletely digested tissue and cell debris in the NaOH 464 digestion step of the fractionation procedure (Taylor and Maher, 2013). The fractionation 465 procedure used by Zhang and Wang (2006) which found 40 and 60% of selenium in 466 crustaceans and bivalves associated with the granule fraction used a shorter NaOH digestion 467 step, 10 minutes rather than the 60 minutes used in this study, so incomplete digestion of the 468 tissue and cell debris fraction in their study is also a possibility. If this is the case then it is 469 still a reasonable assumption that a fair proportion of this fraction represents detoxified 470 selenium.…”
Section: Mycelia Of the Fungus 425mentioning
confidence: 99%